2020
DOI: 10.1155/2020/3761398
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perioperative Music Listening on Patient Satisfaction, Anxiety, and Depression: A Quasiexperimental Study

Abstract: Background. The effect of perioperative music listening has been proven to relieve preoperative anxiety and depression, while improving patient satisfaction. However, music listening has not been extensively studied in Singapore. Therefore, the primary aim of our study is to investigate the patient satisfaction towards perioperative music listening in the local setting. The secondary aim is to investigate the effect of perioperative music listening in reducing patient surgery-related anxiety and depression. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 17 publications
(18 reference statements)
1
23
0
Order By: Relevance
“…In this field, music has the capacity of adjusting emotional stats and promotes mind-body interactions widely accepted for promoting relaxation in health care. In addition, there are many old and new findings that distraction reduces the distress or pain during medical treatments ( 10 , 23 ). In our study, patients who listened to music reported a high level of satisfaction with the endoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this field, music has the capacity of adjusting emotional stats and promotes mind-body interactions widely accepted for promoting relaxation in health care. In addition, there are many old and new findings that distraction reduces the distress or pain during medical treatments ( 10 , 23 ). In our study, patients who listened to music reported a high level of satisfaction with the endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The use of music is already recommended by national, European and international guidelines but with up to now poor evidence (5,7,8). Previous studies have examined the impact of music during various endoscopic procedures, but the results remain inconclusive (9)(10)(11)(12)(13)(14)(15)(16). A major limitation is the lack of objective measurement of patient satisfaction after propofol sedation due to the known euphoric effect of the agent.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al [15] reported difference in mean (SD) HADs anxiety between pre-and post-intervention in music experiences as 4.61 (4.08). The calculated sample size of 70 was based on the following assumptions: considering a conservative mean (SD) HADS difference as 2.0 (8.0), level of significance as 5%; power as 90%.…”
Section: Sample Size Calculation and Statistical Analysismentioning
confidence: 99%
“…Tan et al [28] reported difference in mean (SD) HADs anxiety between pre-and post-intervention in music experiences as 4.61 (4.08). The calculated sample size of 70 was based on the following assumptions: considering a conservative mean (SD) HADS difference of 2.0 (8.0), level of signi cance as 5% and power as 90%.…”
Section: Sample Size Calculation and Statistical Analysismentioning
confidence: 99%